Applied Gratitude Therapy in Cerebral Palsy’s Caregiver to Reduce Subjetive Burden: A Single-Case Design - Siti Rahmah; Muhana Sofiati Utami (Faculty of Psychology, Universitas Gadjah Mada, 2023)
The task of caregivers could potentially lead to an experience that produces negative emotions within themselves. The negative emotions will ultimately have implications for creating a subjective burden on caregivers. This study aims to determine the effect of gratitude therapy to reduce the subjective burden on cerebral palsy caregivers. Participants in this study were 3 caregivers of cerebral palsy whose children had motor skills at 3-5 GMFCS levels and had subjective burden based on the Zarit Caregiver Burden Scale (ZCBS). The experimental design uses small n single-case type A-B-A. Hypothesis testing is done quantitatively by using visual inspection technique followed by descriptive analysis. The result of this study shows a decrease of subjective burden in all participants.